2022
DOI: 10.1021/acs.jpcb.2c00846
|View full text |Cite
|
Sign up to set email alerts
|

Franck–Condon and Herzberg–Teller Signatures in Molecular Absorption and Emission Spectra

Abstract: Some molecules of chemical and biological significance possess vibrations with significant Herzberg−Teller (HT) couplings, which render the Franck−Condon (FC) approximation inadequate and cause the breakdown of the well-known mirror-image symmetry between linear absorption and emission spectra. Using a model two-state system with displaced harmonic potential surfaces, we show analytically that the FC-HT interference gives rise to asymmetric intensity modification, which has the same sign for all transitions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 29 publications
(64 reference statements)
2
35
0
Order By: Relevance
“…This methodology was used by Dong and co-workers 72 , Guo and co-workers 73 , and Wykes and co-workers 8 ; in all cases providing a significant degree of clarity to the results. For reported treatments straying from the FCCLASSES methodology; Kunda and co-workers 74 developed an exact treatment using a path integral formalism. Despite achieving positive results, they were limited to a small number of discrete normal modes.…”
Section: The Failure Of the Effective Transition Dipole Moment Modelmentioning
confidence: 99%
“…This methodology was used by Dong and co-workers 72 , Guo and co-workers 73 , and Wykes and co-workers 8 ; in all cases providing a significant degree of clarity to the results. For reported treatments straying from the FCCLASSES methodology; Kunda and co-workers 74 developed an exact treatment using a path integral formalism. Despite achieving positive results, they were limited to a small number of discrete normal modes.…”
Section: The Failure Of the Effective Transition Dipole Moment Modelmentioning
confidence: 99%
“… 23 Very few instances of the systematic inclusion of finite-temperature HT effects exist in the literature. 20 , 30 , 31 Our recent work 32 identified analytical symmetry arguments dictating the trends of FC–HT interference within the normal mode approximation and reported numerical calculations incorporating temperature dependence and homogeneous broadening. 32 Non-Condon signatures were also recently found in excitation energy transfer 33 , 34 as well as electron transfer 35 , 36 dynamics.…”
mentioning
confidence: 99%
“… 20 , 30 , 31 Our recent work 32 identified analytical symmetry arguments dictating the trends of FC–HT interference within the normal mode approximation and reported numerical calculations incorporating temperature dependence and homogeneous broadening. 32 Non-Condon signatures were also recently found in excitation energy transfer 33 , 34 as well as electron transfer 35 , 36 dynamics. A theoretical study by Zhang et al 33 , 34 suggested that non-Condon vibronic coupling plays a central role in facilitating electronic–vibrational energy transfer and enhancing the quantum yield in contrast to FC vibronic coupling.…”
mentioning
confidence: 99%
See 2 more Smart Citations